PENGARUH LITERASI KEUANGAN DAN PENETRASI INTERNET TERHADAP INKLUSI KEUANGAN SYARIAH DI INDONESIA (2021 - 2025) - fitria, Savira; anita, efni; rahayu, yunie; soleh, ahmad (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This study aims to analyze the effect of financial literacy and internet penetration on Islamic financial inclusion in Indonesia during the period 2021–2025. The increasing use of digital technology and the development of the Islamic financial industry necessitate a deeper understanding of the factors that influence the affordability and use of Islamic financial products by the public. This study uses a quantitative approach with secondary data obtained from official publications of the Financial Services Authority (OJK), Bank Indonesia, and the Central Statistics Agency (BPS). The analysis was conducted using a multiple linear regression model to test the significance of the independent variables' influence on the dependent variable. The results show that financial literacy has a positive and significant effect on Islamic financial inclusion, particularly through increasing public understanding of Islamic financial principles and the benefits of Islamic products in financial management. In addition, internet penetration has also been proven to have a positive and significant effect, given that the digitization of Islamic financial services such as mobile banking, Islamic fintech, and halal e-wallets facilitates public access to financial products and services. These findings confirm that the synergy between improving financial literacy and expanding digital infrastructure is very important in expanding Islamic financial inclusion in Indonesia. This study is expected to contribute to policymakers, Islamic financial institutions, and digital industry players in formulating effective and sustainable strategies to increase financial inclusion.